Development of pulse selectors for the synchrotron radiation pulses from the Photon Factory 2.5 GeV ring to study multiple photoionization. Issue 15 (January 2020) - Adachi, J; Tanaka, H; Kosuge, T; Ishii, H; Suzuki, I H; Kaneyasu, T; Taniguchi, T; Odagiri, T; Ohtaki, S; Tsuji, Y; Soejima, K; Lablanquie, P; et al.
Synopsis: We have developed three pulse selectors to obtain soft x-ray pulses with repetition rates suitable for electron coincidence measurements. The devices enable us to pick out the light pulse from the solo bunch located in the center of the 364-ns dark gap of the hybrid-filling operation. We report the development status and show some typical results of the coincidence measurements with the pulse selectors.